2005
DOI: 10.1021/es050688l
|View full text |Cite
|
Sign up to set email alerts
|

Dioxiranes Generated in Situ from Pyruvates and Oxone as Environmentally Friendly Oxidizing Agents for Disinfection

Abstract: Dioxiranes generated in situ from pyruvates (alpha-keto esters) and Oxone have been found to be environmentally friendly oxidizing agents for disinfection. These oxidizing agents were highly effective for destruction of various strains of bacteria, fungi, and bacterial endospores in a wide temperature range with exceptional stability. Notably, by using an aqueous solution of methyl pyruvate (1a) and Oxone/NaHCO3, complete destruction of bacteria such as Staphylococcus aureus and fungus Penicillium corylophilum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Peroxomonosulfate ion (HSO 5 − ), the anion of Caro’s acid (H 2 SO 5 ), is considered an inexpensive and environmentally friendly oxidant in several different applications. In addition to high general reactivity, its main advantage over hydrogen peroxide is easier handling. It is available on a large scale in the form of a reasonably stable solid, which is commercially sold under the brand name Oxone (2KHSO 5 ·KHSO 4 ·K 2 SO 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Peroxomonosulfate ion (HSO 5 − ), the anion of Caro’s acid (H 2 SO 5 ), is considered an inexpensive and environmentally friendly oxidant in several different applications. In addition to high general reactivity, its main advantage over hydrogen peroxide is easier handling. It is available on a large scale in the form of a reasonably stable solid, which is commercially sold under the brand name Oxone (2KHSO 5 ·KHSO 4 ·K 2 SO 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…2005). A dioxirane formed from methyl pyruvate and Oxone TM has also been recently reported to kill spores of B. cereus (Wong et al. 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work has shown that spores of Bacillus atrophaeus, a close relative of B. subtilis, are killed effectively by DMDO (Wallace et al 2005). A dioxirane formed from methyl pyruvate and Oxone TM has also been recently reported to kill spores of B. cereus (Wong et al 2006). Bacillus subtilis spores were also killed by DMDO ( Fig.…”
Section: Killing Of Spores Of Different Strains By Dmdomentioning
confidence: 86%
“…The examination of reactions using Oxone compared to others could also be interesting. On one hand, it is considered to be environmentally friendly , , and on the other, the mass charge in relation to most substrates is large , because the molecular weight relative to the amount of oxygen it delivers is high.…”
Section: Discussionmentioning
confidence: 99%